Travelling Route Optimisation for Tourist Attractions Places in Malacca - Tan, Q-Yee; Mahathir Mohamad; Kek Sie Long (Enhanced Knowledge in Sciences and Technology, 2024)
Malaysia is ranked as the second most-visited country in Southeast Asia and tourism stands as the third-largest contributor to the country’s GDP. Malacca is a state renowned for its rich cultural and historical significance that is loved by tourists. The lack of itinerary planning poses a significant challenge to travellers which is potentially leading to inefficiencies and time wastage. The travelling salesman problem (TSP) is an np-hard problem that can be used to find the optimal solution. The objective of the research is to develop a comprehensive tourist network encompassing all 17 tourist attractions places in Malacca. The genetic algorithm (GA) method is applied by using MATLAB to calculate the shortest route and minimise travel time. A suggested travelling route is formed to assist tourists in making their travel decisions. This contributes to the efficient planning of tourist itineraries to ensure a seamless and enjoyable exploration of the diverse attractions in Malacca. The data such as attractive places, locations and distances is collected through different sources. The results show that the optimal route for the tourist attractions places is 102.411km. The proposed travel route optimization approach not only caters to the preferences and interests of tourists but also aligns to minimise overall travel time and travel distance, thereby enhancing the overall tourist experience by providing a simple and easily understandable tourist network.